High-efficiency water collection on biomimetic material with superwettable patterns. Issue 84 (8th September 2016) - Zhu, Hai; Yang, Fuchao; Li, Jing; Guo, Zhiguang
Abstract : A superhydrophilic surface with two superhydrophobic circular patterns was successfully prepared, which showed outstanding fog-harvesting efficiency with a water collection rate (WCR) of 1316.9 mg h −1 cm −2 . The water collection process can be repeated 10 times without obvious variation in the WCR. Abstract : A superhydrophilic surface with two superhydrophobic circular patterns was fabricated via a simple and rapid route, showing outstanding fog harvesting properties with a water collection rate (WCR) of 1316.9 mg h −1 cm −2 . Water collection can be repeated on the sample 10 times without obvious change in the WCR.